2012
DOI: 10.1159/000341732
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Dilatation after Haemodialysis Is Determined by the Volume of Fluid Removed and Fall in Mean Arterial Pressure

Abstract: Background/Aims: The effects of haemodialysis on the microcirculation are poorly understood. This study examined the changes in small vessel calibre. Methods: 24 patients (including 12 males, median age 62.5 years, range 30–87) underwent digital retinal photography immediately before and after routine haemodialysis. Arteriolar and venular calibres were measured from the images by a trained grader using a highly reproducible, computer-assisted method. Results: Patients had an average 2.0 ± 0.3 litres of fluid r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…The increased cell metabolism seen at the end of a HD session could be caused by the acute withdrawal of liquid taking place during HD, which reduces interstitial edema and the external pressure on the microcirculation, also triggering an increased dilatation of the peripheral capillaries. 19 Vascular dilatation can be further provoked by complement activation and endothelial production of cytokines and prostacyclins, which occurs during HD, 17,20 as well as by administration of vasodilating antihypertensives, 4 which were common in our patient sample (70% of the ESRD patients were on calcium antagonist therapy). The improvement in thenar cell metabolism may also be related to the increase in oxygenated hemoglobin levels at the end of the HD session.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The increased cell metabolism seen at the end of a HD session could be caused by the acute withdrawal of liquid taking place during HD, which reduces interstitial edema and the external pressure on the microcirculation, also triggering an increased dilatation of the peripheral capillaries. 19 Vascular dilatation can be further provoked by complement activation and endothelial production of cytokines and prostacyclins, which occurs during HD, 17,20 as well as by administration of vasodilating antihypertensives, 4 which were common in our patient sample (70% of the ESRD patients were on calcium antagonist therapy). The improvement in thenar cell metabolism may also be related to the increase in oxygenated hemoglobin levels at the end of the HD session.…”
Section: Discussionmentioning
confidence: 87%
“…Patients with ESRD are permanently exposed to uremic toxins which are poorly removed by HD and induce endothelium-dependent vasodilatation, elevated soluble biomarkers of endothelial dysfunction, and increased oxidative stress. 19,28,29 Traditional risk factors, such as age and hypertension, have been associated with changes in endothelial function, 30,31 and therefore might be responsible for modification of vascular elasticity. Further, hypertensive patients on HD may have more severe vascular damage, because in parallel with progression of endothelial impairment, these patients show a decrease in total vascular dilatative capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Tow et al . demonstrated that the central retinal venules were maximally dilated immediately after haemodialysis by measuring the retinal vascular calibre on the retinal fundus photograph 41 . These changes may influence the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate features were hemorrhage, microaneurysms, cotton wool spots and exudates, and severe retinopathy was characterized by optic disc swelling. However these abnormalities are not permanent, and hemorrhage, exudates and papilledema may resolve, and small vessel caliber, even in CKD5, can increase in response to stressors such as dialysis [26]. Improvements in small vessel damage could occur post-transplantation because of better blood pressure control and resolution of renal failure-induced inflammation.…”
Section: Discussionmentioning
confidence: 99%